2022
DOI: 10.2147/lctt.s288535
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Emerging Therapeutic Options for Malignant Pleural Mesothelioma

Abstract: The treatment paradigm for malignant pleural mesothelioma (MPM) has changed little in the last 18 years. Radical intent treatment, consisting of surgical resection, radiotherapy and chemotherapy, has been offered to a highly select few; however, there is little randomised evidence to validate this approach. Prior to 2020 chemotherapy with platinum and an anti-folate was the only intervention with randomised evidence to demonstrate improved overall survival (OS) in MPM. No systemic therapy had been demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…Treatment methods such as immunotherapy, immune checkpoint inhibitor treatments, new targeted immune treatments, and tumor treating fields are also being developed. [ 11 ] Epithelioid type and an early-stage disease show a solid survival chance following a surgical treatment. [ 12 ] In addition to its high aggressiveness, the mean overall survival (OS) time of MPM (regardless of tumor stage) is 9 to 17 months (averagely 12 months).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment methods such as immunotherapy, immune checkpoint inhibitor treatments, new targeted immune treatments, and tumor treating fields are also being developed. [ 11 ] Epithelioid type and an early-stage disease show a solid survival chance following a surgical treatment. [ 12 ] In addition to its high aggressiveness, the mean overall survival (OS) time of MPM (regardless of tumor stage) is 9 to 17 months (averagely 12 months).…”
Section: Introductionmentioning
confidence: 99%
“…Pt compounds have been used for cancer treatment since the 1970s and even nowadays, in the era of targeted therapies and immunotherapies, they form the backbone of systemic therapy in several solid tumors including PM [10]. Nevertheless, their contribution to OS improvement remains moderate [23]. Importantly, a pivotal cause of therapeutic resistance may be the insufficient drug penetration into the tumor tissue itself [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the last 10 years, different surgical positive experiences have been reported in Europe, China and the United States, and the use of HITHOC for MPM has also been expanded. As a result of this increase, many systematic reviews have been recently published and all of them confirm a longer survival when HITHOC is added to P/D (35)(36)(37). In a recent systematic review and meta-analysis (8), 762 patients treated with HITHOC have been compared to the control group that did not receive HITHOC.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses have concluded that EPP was associated with more postoperative mortality and morbidity in comparison with P/D. It was also concluded that EPD decreased mortality and morbidity by 2.5 folds and that it improved survival (15,22,(34)(35)(36)(37). MPM symptomatically; however, several studies observed that its surgical complications risks weigh more than the possible benefits and that VATS pleurodesis is a more effective and less invasive method (3) (Figure 3).…”
Section: Debulking Surgerymentioning
confidence: 99%